SYMBOL OF WESTERN NEO-ORIENTALISM CRITICISM IN “MS. MARVEL” - Robingah, Robingah; Firstiyanti, Aulia Haris; Ilafi, Afiliasi; Suyudi, Suyudi; Sari, Mulya (Universitas Gunadarma, 2023)
The aim of this article is to construct a critique of Western neo-orientalism through the film medium. Film is a product of popular culture. After 9/11, the concept of neo-orientalism emerged in the West, especially in America, which considers everything that is not